Differentiation syndrome with lower‐intensity treatments for acute myeloid leukemia. Issue 6 (18th March 2021) - Fathi, Amir T.; Stein, Eytan M.; DiNardo, Courtney D.; Levis, Mark J.; Montesinos, Pau; de Botton, Stéphane
Abstract: Differentiation Syndrome (DS) has been identified in a subset of patients undergoing treatment with novel classes of differentiating therapies for acute myeloid leukemia (AML) such as IDH and FLT3 inhibitors. While DS is a well‐known treatment‐related complication in acute promyelocytic leukemia (APL), efforts are still ongoing to standardize diagnostic and treatment parameters for DS in AML. Though the rates of incidence vary, many of the signs and symptoms of DS are common between APL and AML. So, DS can lead to fatal complications in AML, but prompt management is usually effective and rarely necessitates interruption or discontinuation of AML therapy.